Assessment of Physico-Chemical Properties and Enumeration of Coliform in Domestic Water Sources in Pindiga (Journal of Environmental Bioremediation and Toxicology, 2022)
This study was conducted to determine the level of contamination of domestic water sources in Pindiga, Akko Local Government, Gombe State, to observe the trend of quality change of these water sources, if any. Water samples were collected and analyzed for the presence of coliforms and physicochemical quality using standard methods. The results show that the mean value recorded for the physicochemical parameters and the total coliform count among the domestic water sources were within stipulated limits of WHO and NSDWQ except for the chloride mean value of 444.9±437.3 mg/L recorded in borehole water, Biochemical Oxygen Demand means value of 154±8.58 mg/L (hand dug well) and 166.83±32.67 mg/L (borehole) and total hardness mean value of 626.5±510.26 mg/L recorded in hand dug well. Although most of the Physicochemical parameters and the total number of coliforms in domestic water sources were within acceptable limits, continuous monitoring and quality assessment of these domestic water sources in relation to their purification process is needed to maximize safety and healthy life for everyone.
Keywords: Coliform; Domestic Water; Borehole; Hand dug well; Pindiga